2008
DOI: 10.1088/0022-3727/41/8/085301
|View full text |Cite
|
Sign up to set email alerts
|

Surface conduction electron emission in palladium hydrogenation nanogaps

Abstract: A nanometre scale gap (nanogap) structure in palladium strip fabricated by hydrogen absorption under high-pressure treatment was proposed and applied to the surface conduction electron emitter for flat panel displays. In this paper we demonstrate that the structure possesses different high field-emission efficiencies with low turn-on voltages and high focused capability, compared with the conventional type. An experimentally validated simulation is conducted to investigate the field-emission characteristics of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…For investigating the field emission properties in SCE, the FDTD-PIC [16][17][18][19] codes are implemented. Starting from a specified initial state, we simulate electrostatic fields as its evolution in time.…”
Section: Structure and Simulationmentioning
confidence: 99%
“…For investigating the field emission properties in SCE, the FDTD-PIC [16][17][18][19] codes are implemented. Starting from a specified initial state, we simulate electrostatic fields as its evolution in time.…”
Section: Structure and Simulationmentioning
confidence: 99%
“…However, limited size control issues with these techniques represent a critical disadvantage. Alternatively, there are other novel fabrication techniques, such as those based on a molecular ruler,14–16 chemical deposition,17, 18 tilted‐angle shadow evaporation,19–21 and on the focused ion beam (FIB) method 22–24. Although numerous nanogap fabrication methods have been reported, it remains challenging to manufacture controllable and reliable nanogap electrodes in large numbers.…”
Section: Introductionmentioning
confidence: 99%
“…Tsai 4,5 proposed the use of focused ion beams (FIBs) to produce nanogaps on a palladium thin film and the use of hydrogen plasma treatment to increase the edge roughness of the nanogap. Lo [7][8][9][10] found that, in terms of the field-emission properties, a nanogap structure with an inclined protrusion cathode in a palladium strip fabricated by hydrogen absorption is superior to a conventional nanogap structure with a coplanar cathode. Wu 11 applied a conductive film structure with a wasp-waisted shape to control the formation positions of fissures.…”
Section: Introductionmentioning
confidence: 99%